JUSTICIABILITY OF ECONOMIC, SOCIAL AND CULTURAL RIGHTS IN INTERNATIONAL LAW AND ITS FUTURE IMPLEMENTATION IN INDONESIA - Handayani, Irawati (Faculty of Law, Universitas Sebelas Maret, 2018)
Economic, social, and cultural rights are categorized as second generation of rights in the concept of international human rights law. Due to its distinction with first generation right, which is civil and political right, it leads to the differentiation of justiciability of second generation rights. It’s quite often that the fulfillment of economic, social, and cultural rights is postponed, while on the contrary civil and political rights have to be accomplished immediately. The query of justiciability of economic, social, and cultural rights rottenly links with the responsibility of state parties on implementing the rights enumerated in ICCPR or ICESCR. Referring to Article 2 of ICESCR, the implementation of rights stated in ICESCR could be in progressive manner and usually this article is used as an example to not fulfill the right immediately. This article will elaborate further the implementation of protection of economic, social, and cultural rights in another country particularly in South Africa and compare it with Indonesia in order to achieve an ideal form of justiciability of this second generation of rights.